LITERASI SENI DAN BUDAYA PADA ANAK MELALUI MINI WORKSHOP UNTUK MENINGKATKAN PEMAHAMAN KESENIAN TRADISIONAL - Charisma Dina Wulandari; Tsabdany Tzarauliarany Anagusti; Aura Aditra Aryshinta; Marselin Diana; Yani Tandyana; Yani Hendrayani (Qardhul Hasan: Media Pengabdian kepada Masyarakat, 2024)
The presence of art and culture provides opportunities for children to develop creativity and multicultural cultural awareness. Therefore, it is essential to provide skills and cultural education to children to acquire understanding and insights into artistic and cultural literacy from an early age. However, the reality is that 48% of children in RPTRA Bahari have limited access to knowledge about arts and cultural literacy. Therefore, it is important to build awareness of this literacy tradition through activities such as exposing materials on arts and culture literacy, conducting a mini workshop on ondel-ondel dance, and engaging in meronce activities. The purpose of the material exposition activity, mainly related to culture and art literacy, is to enhance the interest and knowledge of children in RPTRA Bahari regarding culture and art. The methods employed in these activities include preparation, implementation, program evaluation, and reporting. The results of these activities demonstrate the children's interest in arts and culture in RPTRA Bahari, as well as an increased fascination among children in acquiring knowledge about cultural and artistic literacy after participating in the mini-workshop on arts and cultural literacy.